PHARMACOCORRECTION OF NEUROTOXIC LESIONS CONSEQUENCES IN SEVERE FORMS OF ACUTE POISONING WITH ETHANOL: NEUROPROTECTIVE EFFECTS OF ANGIOLIN - Belenichev, I.F.; Pavlyuk, I.V.; Kucherenko, L.I.; Abramov, A.V. (World of Medicine and Biology, 2016)
The work deals with the pharmacocorrection of neurotoxic lesions in severe poisoning with ethanol. Experiments have been conducted on 60 white outbred male rats with weight from 160 to 180 grams. Acute alcohol intoxication was modeled by a single intragastric administration of 25% ethanol solution, 22.4 g per kg. This model is accompanied by psycho-neurological changes as well as by pathobiochemical and morphohistological disorders in brain. It appears to be effective to use drugs which have special neuroprotective properties, have an effect on main biological processes in organism and give the possibility to improve the treatment efficacy in patients. Potential original drug “Angiolin” - (S)-2,6-diaminohexanoic acid 3-methyl-1,2,4-triazolyl-5-thioacetate, worked out by “Pharmatron” Scientific-and-Production Association, is of great interest in this aspect. “Angiolin” was administrated singly intraperitoneally 30 min before ethanol administration (prophylactic regimen) and 30 min after ethanol administration (therapeutic regimen) in dose 50 mg/kg. Mildronate was used as reference preparation in the same regimen in dose 100 mg/kg. This experiment included 6 groups of animals; each group consisted of 10 animals. The severity of CNS functions damage was evaluated taking into consideration orienting-exploratory behavior reactions in the “open field” test - vertical and the horizontal motor activities, grooming, sniffing the holes were registered. Five microns-thick microscopic sections of CA-1 zone of hippocampus were deparaffinized and stained to determine the nucleic acid with gallocyanin-chrome alum after Einarson. The morphometric study was performed on the microscope Axioskop (Ziess, Germany) and results were rendered with computer hardware and software system for digital image analysis VIDAS. The research results are processed using the statistical package of licensed program «STATISTICA® for Windows 6.0» (StatSoft Inc., № AXXR712D833214FAN5). The rats underwent acute heavy poisoning with ethanol on the background of single preventive or subsequent administration of Angiolin in dose 50 mg/kg intraperitoneally showed significant improvement in orienting-motor activity as compared with those of the control group. Thus, single administration of Angiolin in therapeutic and especially in prophylactic regimen leveled disturbances of complex forms of behavior after acute heavy poisoning with ethanol: research activity, spatial orientation and motivation level. In rats underwent acute heavy poisoning with ethanol on the background of preventive or subsequent administration of Angiolin the features of orienting-motor activity corresponded to the criteria of non-associative learning that proved high neuroprotective and nootropic effect of the drug directed on the restoration of the natural processes of retention and decay of the skill. Intraperitoneal administration of Angiolin in dose 50 mg/kg in therapeutic and especially in prophylactic regimen to rats underwent acute ethanol intoxication led to significant increase of the density of neurons of the hippocampus CA1 zone, increase of RNA content in them and decrease of the number of neurons with apoptotic features. Neuroprotective activity of Angiolin in prophylactic and therapeutic regimen of administration to animals underwent acute heavy ethanol poisoning was significantly higher than the effect of Mildronate (100 mg/kg), administered under the same conditions.